Evaluation of cooperative security and coupling coordination of water-energy-food-ecosystems nexus: a case study of Yulin City - Jiaqi Sun; Jianyun Zhang; Xiaojun Wang; Yonggang Liu; Jie Zhang; Xu Zhang; Dazhi Li (Water-Energy Nexus)
This study focuses on the water scarcity issue in Yulin City, Shaanxi Province, and explores the coordinated development of water, energy, food, and the ecological environment (WEFEco) in the region. Yulin faces significant challenges due to its scarce natural resources and rapid economic and social development. The mismatch between available water resources and the demands of energy production, food production, and ecological water use has intensified the interdependence and competition among these sectors, becoming a major constraint on high-quality development. To assess the collaborative security and coupling coordination of Yulin’s WEFEco nexus, this study constructs an evaluation indicator system and model, analyzing statistical data from 2000 to 2020. The results show that the synergetic security index of Yulin’s WEFEco nexus fluctuated upward over the period, indicating an improvement in the overall synergetic security. However, the index remains below 0.6, suggesting that further strengthening of water resource management, optimizing energy production, improving food production capacity, advancing ecological protection, and enhancing interdepartmental cooperation are necessary. The analysis also reveals four stages of coupling coordination in Yulin’s WEFEco nexus: 1) 2000–2008, a transitional stage with rapid economic growth but lagging management; 2) 2009–2014, a basic coordination stage with improved management measures, though still insufficient; 3) 2015–2017, a period of decline in coordination, characterized by near-coordination development and mild disorder due to environmental and social changes; and 4) 2018–2020, a basic coordination stage where reforms and policies led to improved coordination. The study highlights the important role of economic, policy, and environmental factors in promoting the coordinated development of the WEFEco nexus.